Effect of Student Union committee participation in retrospect, Wisconsin State University, La Crosse, 1960-70 - Macgillivray, Thomas (My University, 1970)
The purpose of this descriptive study was to investigate the effect of Student Union committees at Wisconsin State University, La Crosse. Areas concentrated on to measure effect included acceptance into graduate school, acquisition of employment, and post-college citizenship. General questions on the value of committee participation and just why did these former students join a Student Center committee also played a role i n the investigation.
Keywords: Student unions.; Student activities, Wisconsin, La Crosse.; Wisconsin State University (La Crosse), Student Union.